2022
DOI: 10.3389/fneur.2022.849804
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sleep Pattern in School/Work Performance During the COVID-19 Home Quarantine in Patients With Narcolepsy

Abstract: ObjectivesNarcolepsy patients were observed improvements in their academic performance during the COVID-19 home quarantine. Therefore, we aim to investigate the influence of sleep behavioral changes on school/work performance in narcolepsy patients during the home quarantine.MethodsPatients admitted to Shandong Provincial Qianfoshan Hospital from Jan 1, 2017 to Jan 1, 2021 who were diagnosed with narcolepsy were studied by online questionnaires in two different periods (during and 1 year after the COVID-19 hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Such adaptations are likely to relieve the pressure exerted on patients, as suggested by reports of positive consequences of remote work/school during the COVID 19 lockdown. 41, 42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such adaptations are likely to relieve the pressure exerted on patients, as suggested by reports of positive consequences of remote work/school during the COVID 19 lockdown. 41, 42…”
Section: Discussionmentioning
confidence: 99%
“…Such adaptations are likely to relieve the pressure exerted on patients, as suggested by reports of positive consequences of remote work/school during the COVID 19 lockdown. 41,42 Psycho-behavioral disorders are frequent and affect multiple dimensions in NT1, although their determinism (reaction to symptoms such as somnolence or cataplexy or to the disability and stigmatization associated with the disease, or direct involvement of orexinergic dysfunction) is not fully understood. 5,6,12,13,15,43,44 We observed that depression was strongly associated with professionnal prognosis with a possible bidirectional link: depression preventing patients from performing well at work and psychopathological risk being aggravated by academic/professional failure.…”
Section: Discussionmentioning
confidence: 99%
“…During the 2020 pandemic years to the present, much research has focused on job performance. Among the frequent factors related to work performance during the pandemic were, e.g., fear of COVID-19 ( Sarwar et al, 2022 ), remote work ( Adekoya et al, 2022 ; Kirchner et al, 2021 ; Toscano and Zappalà, 2021 ; Kifor et al, 2022 ), sleep patterns ( Zhao et al, 2022 ), communication ( Amano et al, 2021 ), burnout syndrome ( Raja et al, 2022 ), or stress ( Kumar et al, 2021 ), etc.…”
Section: Introductionmentioning
confidence: 99%